THE ATTITUDE OF REJECTION OF COLONIALISM IN ACEH AS REFLECTED IN HIKAYAT PRANG SABIL BY TEUNGKU CHIK PANTE KULU - MUYASSIR (Department of English Education, Faculty of Teacher Training and Education, Almuslim University, 2021)
Hikayat is a cultural product of the Malay peoples in the form of ancient prose. The use of language style and ancient words in a saga is one of the causes of the unpopularity of the saga at this time. At present saga is only intended as an art product and research material to examine the culture of a Malay nation. This research is intended to determine the impact of Hikayat Prang Sabil by Teungku Chik Pante Kulu during the times of the struggle of the Acehnese people against Dutch colonialism and also to find out how the role of the spirit of Hikayat Prang Sabil after the Aceh-Dutch war ended to the present. The results of this study prove that the Hikayat Prang Sabil played a major role in the struggle of the Acehnese people against Dutch colonialism, where Hikayat Prang Sabil became a moral force and also as a center of gravity that united all elements of Acehnese society to fight on one main goal, namely to fight against infidels for defend the religion and national pride. Hikayat Prang Sabil became a tool to spread the call of Jihad Fi Sabilillah, with the aim of recruiting and also raising funds to fight. However, the enthusiasm of the people after hearing Hikayat Prang Sabil was beyond expectation. Not only is it momentary, but the contents of Hikayat Prang Sabil also influenced the sociological behavior patterns of the Acehnese people at that time. so that the name Atjeh-Moord appears, namely the behavior in which the people of Aceh become infatuated with the idea of jihad that makes them kill every infidel they meet, even from non-military groups.